As escolas família agrícola no território goiano: a pedagogia da alternância como perspectiva para o desenvolvimento e o fortalecimento da agricultura camponesa - JESUS, José Novais de (2010)
This survey tends to understand the contributions of the Escolas Família Agrícola (EFAs) from Goiás, Orizona and Uirapuru municipality to the strengthening of the countryside agriculture. The construction of EFAs in Goiás territory started in 90 s in Goiás municipality. This way, these experiences in the Alternance Pedagogy are being made by the Centros Familiares de Formação por Alternância (CEFFAs), the EFAs and the Casas Familiares Rurais (CFRs) that working th e four pillars of the Altenance Pedagogy. So, the EFAs was thought to attend specifically the youngs of the country and to search alternatives before the difficulties that the countryside farmers face it out about of knowledgement of agricultural techniqu es. The Professional background of the Alternative Pedagogy has gotten to the country youngs the development of new agricultural and cattle -breeding practices to have in view increasing the earn and to stay in the country. This survey has the comprehension that only the school can t solve social and techniques problems and it s necessary to invite another intutitions to reach common actions in the political and pedagogy camp. The survey also showed that EFAs facing a lot of of challenge against impositions of educational politics, devaluation of the countryman and the exaltation of the business of the country. The technical graduation isn t answering the expectatives of the students and the families in its right sense, because of lack of the professionals to assume the control in the professionalizing education. It s showed that pedagogics coordination and the associations has difficult to understand and to be in control of instruments of alternance , showed in the lack of continued graduation from the monitors/teachers that are acting in the education of the country, this fault are present in the EFAs. Still there are difficulties to understand EFAS as educational movement, by the contradictions that is shoed in these schools, reproducing the traditionalism logical. But EFAs and the Alternative Pedagogy remain the alternative of passable education in the countryside, because this method gets to integrate school, family and community in the search of solutions to the problem of the countrymen. This survey put emphasis in the constructions of the country territories by the territorial dispute, presents in the occupations and resistance of the agricultural countrymen. The role of EFAs in this situation and how their peda gogic actions contribute in the territorial development and the strengthening of the countryside of the countryside agriculture. Even so, there is a discussion about the geography instruction and its relation with the country. This work was made in Gimonet (2007), Fernandes (2004), Raffestin (1980 ) Queiroz (2004) and Azevedo (1999) theory centered.